The Effects of Social Engagements to the Academic Pursuits on Nursing Students - Dy, Mizaki Alexza; Bactol, Charlotte; Dacera, Divine; Payumo, Mary Agnes; Raguindin , Sandhie; Tayo , Ica Ella; Merced, Joel John Dela; Sedeno , Carlos Kurt; Salcedo , Trinidad J.; Jecino , Liza May B.; Palig-ad, Abigail P.; Pambuan , Susana; Abonalla , Arby James; Aggari , Michael (MALATA SAINS INDONESIA, 2025)
This study investigates how social engagement impacts third-year nursing students' academic performance and well-being. While social support benefits academic engagement, more research is needed on nursing students’ unique challenges and social experiences. This quantitative correlational study investigated the relationship between social engagements and academic achievements among third-year students. Data were collected through face-to-face surveys using Likert scale questions from 306 participants at a prominent school in Quezon City. Purposive sampling was employed, focusing on students involved in extracurricular activities. Findings revealed that majority of respondents were 21 years old (55.23%), predominantly female (73.86%), and had a weekly allowance below PHP 1,000 (51.31%). Social engagements was generally low, with the highest participation in birthday celebrations (mean: 3.085,